1993
DOI: 10.1017/s0022215100122613
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin and epistaxis — a case controlled study

Abstract: Patients anticoagulated with warfarin form a small proportion of thos se admitted with epistaxis annually to ENT units. The authors formed the impression that such patients spend longer in hospital and have more complicated management than controls. A prospective age and sex matched controlled study of 20 consecutive patients admitted with epistaxis whilst anticoagulated was performed. This showed thath these patients spent significantly longer in hospital than cntrols, with an additional expense in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 0 publications
2
24
2
Order By: Relevance
“…Denholm et al showed that warfarin not only leads to a higher incidence but also to more complicated bleeding episodes. 15 Analogous to the latter study, we were able to demonstrate that ASA patients not only have a higher severity score in comparison with the rest of the patients, but we could also conclude that the rate of surgical intervention is even higher than in the coumarin group. There may be two explanations for this finding.…”
Section: Discussionsupporting
confidence: 74%
“…Denholm et al showed that warfarin not only leads to a higher incidence but also to more complicated bleeding episodes. 15 Analogous to the latter study, we were able to demonstrate that ASA patients not only have a higher severity score in comparison with the rest of the patients, but we could also conclude that the rate of surgical intervention is even higher than in the coumarin group. There may be two explanations for this finding.…”
Section: Discussionsupporting
confidence: 74%
“…Tay et al indicated that patients who had been prescribed aspirin had a relative risk of hospital admission for epistaxis of between 2.17 and 2.75, depending on the control group used [14]. Denholm et al showed that patients anticoagulated with warfarin spent significantly longer in hospital than controls [24]. On the other hand, Srinivasan et al demonstrated that there was no significant difference in the mean hospital stay between the warfarin and non-warfarin groups, and warfarin can be continued x 2 = 7.09, p = 0.008. safely in patients with epistaxis, in appropriate circumstances [25].…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation and antiplatelet therapy is associated with an increased risk of epistaxis. Previous reports have shown that antithrombotic therapy is used in up to 60% of patients admitted for epistaxis, and is associated with longer hospital stays and higher rates of readmission …”
Section: Introductionmentioning
confidence: 99%